Development of a Cigarette Smoking Obscenity Scale (CSOS) in adolescents: an exploratory sequential mixed method design - Keshavarzian, Khadijeh (Health Promot Perspect, 2020)
Background: Considering the increasing prevalence rate of smoking among Iranian adolescents,and recent evidence on the relationship between obscenity of smoking and tendency of adolescents towards the behavior, there is a need for an appropriate measurement tool to measure the level of obscenity on cigarette smoking among adolescents. This study was conducted to develop a valid and reliable questionnaire for measuring the obscenity of cigarette smoking in adolescents. Methods: This study was conducted in Tabriz, Iran, using an exploratory sequential mixed methods design. To explain the concept of obscenity and develop the questionnaire’s items, 18 students attended semi-structured individual interviews and 13 others took part in focus group discussions (FGDs) in three groups of 4-5. Extracting and summarizing the codes derived from the interviews, an item pool was developed, from which the initial draft of the scale was provided.Next, the psychometric properties of the scale were assessed using face, content, construct, and predictive validity, as well as internal consistency, and reliability in a sample of 1013 high school students. Results: The 22-item Cigarette Smoking Obscenity Scale (CSOS) was developed based on thecodes derived from qualitative data. Explanatory factor analysis revealed five-factor structure(Negative Attitude; Negative Consequence; Negative Valuation; Inappropriate Relationship; Agateway to addiction). In confirmatory factor analysis, the χ(2)/df ratio was 3.911 for the CSOS five-factor structure. Suitable values were obtained for the goodness of fit indices (GFI = 0.88,AGFI = 0.85, NFI = 0.87, IFI = 0.90, CFI = 0.90, RFI = 0.85, and RMSEA = 0.072). The Cronbach’s alpha and intraclass correlation (ICC) coefficients for the constructs ranged between 0.77 to 0.90 and 0.80 to 0.91, respectively. Conclusion: The validity and reliability of the CSOS was appropriate; therefore, it can be used infuture studies as a suitable tool for measuring the obscenity of cigarette smoking in adolescents.